Magnetic and density characteristics of igneous rocks near the Ukrainian antarctic station Akademik Vernadsky - V. Shpyra; V. Bakhmutov; L. Bakhmutova; D. Gladkochub; A. Koshelev; T. Skarboviychuk; V. Yakukhno (Ukrainian Antarctic Journal, 2014)
As a result of studies of the magnetic properties and density of more than 500 samples of Mesozoic and Paleocene intrusive and volcanic complexes sampled in the western Antarctic Peninsula (Vernadsky base area), new information for the petrophysical characteristics of rocks was obtained. Rocks are characterized by a wide range of values both magnetic (magnetic susceptibility – from 0.0016 to 0.26 SI, natural remanent magnetization – from 0.0045 to 8.37 A/m) and density (from 2.57 to 3.3 g/cm3) parameters. Differences in density and magnetic characteristics of rocks of various petrographic groups fit into the general laws of their changes in rocks from acid to basic compound. Accordingly, the average densities are 2.65, 2.77 and 2.9 g/cm3, the magnetic susceptibility of 0.02, 0.036 and 0.068 SI, natural remanent magnetization – 0.16, 0.3 and 2.08 A/m. New data are the basis for parameterization of gravity and magnetic models which have been calculated for anomalous potential fields.